A Study on Insulation Characteristics of Glass Wool and Mineral Wool Coated with a Polysiloxane Agent - Chan-Ki Jeon; Jae-Seong Lee; Hoon Chung; Ju-Ho Kim; Jong-Pil Park (Advances in Materials Science and Engineering)
The insulation in buildings is very important. Insulation used in the building is largely divided into organic and inorganic insulation by its insulation material. Organic insulation materials which are made of Styrofoam or polyurethane are extremely vulnerable to fire. On the other hand, inorganic insulation such as mineral wool and glass wool is very weak with moisture, while it is nonflammable, so that its usage is very limited. Therefore, this study developed moisture resistance applicable to mineral wool and glass wool and measured the thermal conductivity of the samples which are exposed to moisture by exposing the product coated with moisture resistance and without moisture resistance to moisture and evaluated how the moisture affects thermal conductivity by applying this to inorganic insulation.